Odpowiedzi

2010-02-15T20:01:09+01:00
C) 5a²+15a+20a³
d) 8a³-4a²-8a+4
e) -3k-6k³-18klm
f) -0,25x-0,75y-1,5
g) 5a+0,7a²+10abc
h) 10x⁴+50x²-100x

c)5a²+15a+20a³=
5a(a+3+4a²)

d) 8a³-4a²-8a+4=
4(2a³-a²-2a+1)

e) -3k-6k³-18klm=
3k(-1-2k²-6lm)

f) -0,25x-0,75y-1,5=
5(-0,05x-0,15y-0,3)

g) 5a+0,7a²+10abc=
5a(a+0,14a+2bc)

h) 10x⁴+50x²-100x
10x(x³+5x+10)
1 5 1
Najlepsza Odpowiedź!
2010-02-15T20:01:14+01:00
C)5a²+15a+20a³= 5a(a+3+4a²)

d)8a³-4a²-8a+4= 4(2a³-a²-2a+1)

e)-3k-6k³-18klm= -3k(1+2k²+6lm)

f)-0,25x-0,75y-1,5= -0,25(x+3y+6)

g)5a+0,7a²+10abc= a(5+0,7a+10bc)

h)10x⁴+50x²-100x³= 10x(x³+5x-10x²)
1 5 1
2010-02-15T20:27:05+01:00
C) 5a²+15a+20a³ = 5a(a+3+4a²)

d) 8a³-4a²-8a+4 = 4(2a³-a²-2a+1)

e) -3k-6k³-18klm = -3k(1+2k²+6lm)

f) -0,25x-0,75y-1,5 = -0,25(x+3y+6)

g) 5a+0,7a²+10abc = a(5+0,7a+10bc)

h) 10x⁴+50x²-100x³ = 10x²(x²+5-10x)